1999
DOI: 10.1074/jbc.274.16.10807
|View full text |Cite
|
Sign up to set email alerts
|

Selective Stimulation of Hepatitis C Virus and Pestivirus NS5B RNA Polymerase Activity by GTP

Abstract: NS5B of the hepatitis C virus is an RNA template-dependent RNA polymerase and therefore the key player of the viral replicase complex. Using a highly purified enzyme expressed with recombinant baculoviruses in insect cells, we demonstrate a stimulation of RNA synthesis up to 2 orders of magnitude by high concentrations of GTP but not with ATP, CTP, UTP, GDP, or GMP. Enhancement of RNA synthesis was found with various heteropolymeric RNA templates, with poly(C)-oligo(G) 12 but not with poly(A)-oligo(U) 12 . Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 51 publications
(34 reference statements)
4
74
1
Order By: Relevance
“…In sharp contrast, soaking the crystals with rATP, rCTP, or rUTP, even at a 10 mM concentration, does not lead to binding at the surface site, demonstrating the specificity for rGTP. Several studies have shown a specific effect of high rGTP concentrations on the efficiency of RNA synthesis by NS5B (29,30). Luo et al (30) have concluded that the rGTP effect is likely to be related to its incorporation as an initiating nucleotide, which they interpret as being rate limiting for RNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sharp contrast, soaking the crystals with rATP, rCTP, or rUTP, even at a 10 mM concentration, does not lead to binding at the surface site, demonstrating the specificity for rGTP. Several studies have shown a specific effect of high rGTP concentrations on the efficiency of RNA synthesis by NS5B (29,30). Luo et al (30) have concluded that the rGTP effect is likely to be related to its incorporation as an initiating nucleotide, which they interpret as being rate limiting for RNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…An additional distinctive feature of these two polymerases is their ability to initiate replication from an RNA template without the need of a primer (de novo initiation), as reported for HCV (30,34,46) and 6 (31). In addition, it has been shown that high concentrations of riboguanosine triphosphate (rGTP) stimulate RNA synthesis for both the 6 (35) and HCV (29,30) enzymes, presumably by enhancing the efficiency of the initiation process. The cocrystals of the 6 polymerase in complex with a DNA oligonucleotide and rGTP provided the first snapshot of an initiation complex formed by these enzymes (12).…”
mentioning
confidence: 99%
“…Products longer than template length were observed with the replicases from BMV (26), dengue virus (36), turnip crinkle virus (37), and the RdRps from hepatitis C virus (38,39) and poliovirus (40). If all of the unexplained dimeric products are caused by template switch, then RNA recombination in vitro can be directly studied with RNA viruses for which RNA synthesis assays are available.…”
Section: Discussionmentioning
confidence: 99%
“…The focal point of such investigations has been NS5B, which possesses an RNA-dependent RNA polymerase (RdRp) activity and is believed to be the key enzyme catalyzing HCV RNA synthesis (7)(8)(9)(10)(11)(12)(13)(14). Its crystal structure reveals that it contains the classical finger, palm, and thumb subdomains of the polymerases with the unique feature of a more fully enclosed active site tunnel (15)(16)(17), and a recent report by Bressanelli and colleagues (18) has provided additional information about the complex of NS5B with ribonucleotides.…”
mentioning
confidence: 99%